2017
DOI: 10.21276/aimdr.2017.3.6.og1
|View full text |Cite
|
Sign up to set email alerts
|

Maternal and Perinatal Outcome in Obstructed Labour

Abstract: Background: Obstructed labour comprises one of the five major causes of maternal mortality & morbidity in developing countries. It accounts for 5% of all maternal deaths in India unfortunately this preventable condition of obstructed labour still prevails in this part of our country. Our hospital M.K.C.G. medical college being a tertiary care hospital has maximum referred patients from rural areas, viewed in this context this prospective study has been undertaken in department of obstetrics and gynaecology to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 2 publications
(6 reference statements)
0
1
2
Order By: Relevance
“…Besides, this study showed that OL resulted in 8.3% of maternal deaths among cases. This figure is higher than a study done in India, [53,54], Uganda, [26], Sudan, [29], Nigeria, [55], Tanzania, 2% [50], Bangladesh, [52] and Ethiopia, [20]. However, the findings of the current study were lower than a similar study in Sudan, [56].…”
Section: Plos Onecontrasting
confidence: 93%
See 1 more Smart Citation
“…Besides, this study showed that OL resulted in 8.3% of maternal deaths among cases. This figure is higher than a study done in India, [53,54], Uganda, [26], Sudan, [29], Nigeria, [55], Tanzania, 2% [50], Bangladesh, [52] and Ethiopia, [20]. However, the findings of the current study were lower than a similar study in Sudan, [56].…”
Section: Plos Onecontrasting
confidence: 93%
“…The possible variation might be due to delays in referral and treatment of OL, prolonged labour, study setting, sample size and methodological differences between the studies. However, the finding of this study is lower than studies done in Bangladesh [52], India [53,54], Suhul hospital, Ethiopia [20], and Metu Karl hospital, Ethiopia [18]. This might be due to the commitment of the hospital to improve maternal healthcare provision, safe surgery with the senior obstetrician and EMONC service.…”
Section: Plos Onecontrasting
confidence: 75%
“…It is well known that prolonged and obstructed labor are major contributors to the high rate of maternal mortality (Mohapatra et al, 2017). 44,000 women (about twice the seating capacity of Madison Square Garden) lose their lives every year because of complications during pregnancy, and all of them might have been avoided had they lived in a higher-income country (UNICEF, 2018).…”
Section: Significance Of the Studymentioning
confidence: 99%